Optimization of Digital Speckle Patterns and Its Application in Measuring Crack-Tip Deformation Fields of CNTs/PDMS Composites - Liu , Huan (International Journal of Mechanical and Electrical Engineering, 2025)
An improved algorithm for generating digital speckle patterns is proposed. This method introduces a minimum spacing constraint and a multi-shape random distribution strategy to overcome two common limitations of conventional approaches: limited morphological diversity and undesirable overlap at high densities. A comprehensive evaluation was performed using four key parameters: speckle size, mean intensity gradient, systematic error, and random error. The digitally designed speckle patterns were transferred onto a CNTs/PDMS composite via a non-destructive technique. This approach successfully enabled the measurement of deformation fields in the crack tip region under large-strain conditions. Based on the experimental results, the fan-shaped zoning characteristics of the deformation field near the crack tip were analyzed. The experimental results validate that the speckle patterns produced by the proposed algorithm are high-contrast and well-distributed, demonstrating significant potential for applications in fracture mechanics studies of flexible composites.